Effect of Six Weeks of Training with Wearable Resistance Attached to the Forearm on Throwing Kinematics, Strength, and Velocity in Female Handball Players - Andrea Bao Fredriksen; Roland van den Tillaar (Journal of Functional Morphology and Kinesiology)
Background: The aim of the study was to investigate the effect of six weeks of training with wearable resistance attached to the forearm on throwing kinematics, strength, and velocity in experienced female handball players. Methods: Twenty-five female handball players (mean age: 24.7 ± 3.8 y, mass: 72.1 ± 17.6 kg, height: 1.69 ± 0.06 m, and training experience: 14.3 ± 4.9 y) participated and were divided into an experimental group (n = 14) or a control group (n = 11). Both groups participated in the same handball sessions, but the experimental group trained with wearable resistance attached to the forearm during the training sessions. Before and after a training period of six weeks, throwing velocity, strength, and kinematics were tested. Results: The throwing velocity was significantly increased in the experimental group but not in the control group (p = 0.006). Only a few significant kinematic changes were observed, mostly around ball release, in which both groups had increased elbow flexion. The experimental group had a larger shoulder flexion at ball release and a more flexed wrist (p ≤ 0.04). Meanwhile, the control group had a lower shoulder abduction after the training period (p ≤ 0.023). No significant effects were found in the maximal angular velocities, timing of joint angles, angular velocities and in the strength test (p > 0.075). Conclusions: Based on the findings in this present study, it was concluded that training with wearable resistance attached to the forearm increases throwing velocity during the competition season compared to normal throwing training, which was probably caused by the changes in maximal elbow angle and extension velocity and the more flexed wrist at ball release.